â€œKAJIAN KOMPARATIF PRODUK ASURANSI SYARIAH DAN ASURANSI KONVENSIONAL SERTA KESESUAIAN ANTARA KETENTUAN ASURANSI SYARIAH DENGAN PENERAPANNYAâ€ (STUDI KASUS PADA PT. AIA FINANCIAL CABANG KOTA MALANG) - Dellarosa, Evelyn (Jurnal Ilmiah Mahasiswa FEB, 2014)
The purpose of this study is to determine the compatibility between the stipulation of insurance with its application in Insurance Institute of AIA Financial Malang City and to analyze the comparison results between Sharia Insurance Products with Conventional Insurance Products at Insurance Institute of AIA Financial Malang City. The type of research used by the researcher is a qualitative descriptive with a case study approach. Based on the results of research by the author, it can be concluded that the Indonesian society still has a commercial nature. This can be evidenced by the many people who prefer to use conventional insurance that is more financially advantageous compared with sharia insurance that is the benefits are not too large. Yet it is clear to say that riba' or interest is forbidden under Islamic law. In addition, the implementation of the stipulation into practice has not been completely implemented because the researchers still see the difference between stipulation and practice, especially in the akad tabarruâ€™. So it can be said that there is no difference between the conventional and sharia in the terms of practice, but only the differences in behavior, morality, and the term. Keywords: insurance, Akad Tabarru', sharia